Sustainable Liquefied Natural Gas Supply Chain Management: A Review of Quantitative Models - Sara Al-Haidous (18095368) (2019)
Natural gas is an essential fuel in the transitions towards a sustainable energy future as it is considered a cleaner source of fuel when compared to other hydrocarbon sources. To enable natural gas delivery from the producer to consumers, natural gas is liquified to enhance transportation efficiency and reliability. The main contribution of this paper is to develop sustainable LNG supply chain through a review of different sustainable supply chain management tools and assessing their applicability in managing LNG supply chains. Energy security has evolved to include the protection of the entire energy supply chain and infrastructure rather than a consideration for the availability of resources alone. There is a particular focus on coupling sustainability and resilience/risk as part of the need to develop integrated approaches to manage energy supply chains to deliver cargo at minimal cost and environmental impact, and to ensure that supply chains can overcome vulnerabilities withstanding potential disruptions to the supply chain. Outcomes of this review demonstrate the possibility to develop multi criteria models, which consider sustainability dimensions within the LNG supply chains and to integrate parameters that form part of the annual delivery plan ensuring day to day LNG supply chain planning consider multiple objectives. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su12010243